Analisis Terhadap Kebijakan Pemerintah Dalam Mengatur Urusan Pemerintahan Daerah Di Era Desentraliasi Asimetris - Arifin, Firdaus (Fakultas Hukum Universitas Bangka Belitung, 2024)
Asymmetric decentralization in Indonesia is designed to grant special autonomy to regions with unique characteristics; however, its implementation often falls short due to institutional capacity limitations and continued dependence on the central government. This study aims to evaluate the effectiveness of asymmetric decentralization policies in various special autonomous regions of Indonesia, focusing on Aceh, Papua, and Yogyakarta. The research employs a normative and empirical juridical approach, supported by case studies and qualitative data analysis. The findings reveal a significant gap between policy objectives and implementation, attributed to factors such as inadequate local resources and weak coordination between the central and regional governments. The implications of these findings highlight the need to strengthen regional institutional capacity, enhance central government support, and tailor policies to be more context-specific and adaptable to local conditions. This study provides valuable insights for developing more effective and sustainable decentralization policies in Indonesia.